2002
DOI: 10.1161/01.cir.0000012146.07240.fd
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Collateral Formation in Lipoprotein(a) Transgenic Mice

Abstract: Background-Although lipoprotein(a) (Lp[a]) is a risk factor for atherosclerosis, no study has documented the effects of Lp(a) on angiogenesis. In this study, we examined collateral formation in peripheral arterial disease (PAD) model in Lp(a) transgenic mice. In addition, we examined the feasibility of gene therapy by using an angiogenic growth factor, hepatocyte growth factor (HGF), to treat PAD in the presence of high Lp(a). Methods and Results-In Lp(a) transgenic mice, the degree of natural recovery of bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 40 publications
3
46
0
Order By: Relevance
“…Human recombinant HGF has been applied in therapeutic angiogenesis, as a cytokine supplement for patients with arteriosclerosis obliterans. 29 Hepatocyte growth factor is also seen as a significant cardioprotective factor because of its potent angiogenetic properties 14,30 and because HGF can reduce restenosis after balloon injury by enhancing re-endothelialization. 31 On the other hand, plasma HGF levels are elevated in malignancies, 32 patients with atherosclerosis and proliferative diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human recombinant HGF has been applied in therapeutic angiogenesis, as a cytokine supplement for patients with arteriosclerosis obliterans. 29 Hepatocyte growth factor is also seen as a significant cardioprotective factor because of its potent angiogenetic properties 14,30 and because HGF can reduce restenosis after balloon injury by enhancing re-endothelialization. 31 On the other hand, plasma HGF levels are elevated in malignancies, 32 patients with atherosclerosis and proliferative diabetic retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocyte growth factor (HGF) is another endothelial growth factor with potent angiogenetic and mitogenic effects. 13,14 Recently, HGF as well as VEGF are being used in 'therapeutic angiogenesis'. 15,16 Serum HGF levels are elevated not only in patients with hepatic desease.…”
Section: Introductionmentioning
confidence: 99%
“…4 In various animal models, transfection of naked plasmid DNA encoding the human HGF gene has achieved effective angiogenesis. [5][6][7][8][9][10][11] The first human clinical trial of HGF gene therapy for PAD was performed in Japan, and showed that intramuscular injection of naked HGF plasmid was well tolerated. 12 A subsequent multicenter, randomized, double-blind, dose-finding, placebo-controlled, trial performed in the USA showed that an injection of the HGF gene increased the tissue perfusion compared with placebo.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF and bFGF are considered to mobilize and recruit endothelial (progenitor) cells, subsequently accelerating the onset of angiogenesis (7). HGF is an additional important endothelial growth factor with potential angiogenic and mitogenic effects (8). Cotransplantation of ASCs with aspirated fat tissue may improve graft retention due to angiogenic effects.…”
Section: Introductionmentioning
confidence: 99%